Clinical signs, diagnosis and treatment of trichophytosis in guinea pigs - V. O. Sablieva; K. V. Pashkov; O. E. Andriiash; M. V. Bilan; V. V. Zazharskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Dermatophytosis is one of the most common infectious diseases of the skin among animals. Knowledge of such infections is extremely important and will help to reduce the spread of zoophilic infections among humans, especially in close contact with pets, which may be asymptomatic carriers of dermatophytes, and among laboratory animals of vivariums or pet stores. The article describes the clinical, diagnostic and therapeutic aspects of trichophytosis of guinea pigs. The results of our research are important from a scientific and practical point of view, indicating the need for timely detection of sick animals, asymptomatic carriers, and adherence to a preventive strategy that will help prevent the transmission of dermatophytes among animals and humans. Clinical signs were recorded in animals that were in neighboring cages: in one animal – in the form of round lesions with dense gray scales 5–10 mm in diameter on the face. The individual hair tufts were crusted over. In another animal, on the sides and abdomen, dull fur, few round spots covered with thin and dry scales and partial hair loss were noted. Laboratory tests during the life of the animals revealed straight hyphae of septated mycelium of the fungus, arranged in rows, and straight chains of spores inside and outside the hair. The fungus did not fluoresce under a Wood's lamp. Powdery beige colonies, yellowish on the reverse side, were found on Sabouraud agar on day 8 after sowing of pathological material from both patients and animals in contact with patients. The fungus was classified as Trichophyton spp. by morphology and culture properties. The patients were treated orally with terbinafine and topically with imaverol. Sodium hypochlorite was used as a disinfectant to treat hard surfaces, care tools, and cages. Trichophytosis and other zoonotic pathogens have consequences for human health, which emphasizes the need for awareness among pet owners. This plays a key role in protecting the health and safety of both humans and animals, and their harmonious existence.